2011
DOI: 10.1103/physrevb.84.174426
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity susceptibility in two-dimensional spin-orbit models

Abstract: We study the quantum phase transitions in the two-dimensional spin-orbit models in terms of fidelity susceptibility and reduced fidelity susceptibility. An order-to-order phase transition is identified by fidelity susceptibility in the two-dimensional Heisenberg XXZ model with Dzyaloshinsky-Moriya interaction on a square lattice. The finite size scaling of fidelity susceptibility shows a power-law divergence at criticality, which indicates the quantum phase transition is of second order. Two distinct types of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 90 publications
0
38
0
Order By: Relevance
“…Experiments for the iridates, however, found a zig-zag AFM order [6][7][8][9]. These progresses drive a number of further researches [10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…Experiments for the iridates, however, found a zig-zag AFM order [6][7][8][9]. These progresses drive a number of further researches [10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…This quantum phase transition at ∆ = −1 is infinite-order in d = 1 and second-order in d = 2. 133 The ground-state energy peak at ∆ = −1 was also observed by Monte Carlo simulations on square lattice 134 , while the concurrence peak at ∆ = −1 was observed in d = 2 135 as well as in d = 1 123,131,135,136 . We should emphasize that the relevance of entanglement with the quantum phase transitions has been suggested by many authors before.…”
Section: Zero-point Quantum Phase Transitionsmentioning
confidence: 57%
“…Fortunately, with the development of quantum information, various information measures, e.g., quantum coherence, entanglement entropy, and fidelity, can help us to study quantum critical phenomena in spin chains. It is found that the quantum critical points can be well characterized by both the ground-state entanglement and fidelity on large system [27][28][29][30][31][32][33][34]. In this paper we study the entanglement, coherence and fidelity of the spin-1/2 Heisenberg alternating chain under a transverse magnetic field, and finally the phase diagram will be given.…”
Section: Introductionmentioning
confidence: 99%